Effect Of Addition Of Molasses And Period Of Preservation On Physical And Nutritional Properties Of Maize Stover Silage - Bostami, ABMR; Khan, RI; Amin, MR; Sarker, NR; Pervage, S; Hasan, K (Bangladesh Journal of Animal Science, 2012)
An experiment was undertaken to determine the physical and nutritional properties, in vitro digestibility and metabolizable energy of maize stover ensiled with different levels of molasses at three different ensiling times (45, 90 and 135 days). Maize stover was collected from field immediately after harvesting the corn, chopped and were preserved in plastic containers under normal condition and were treated as control (T0) (sample only), sample ensiled without additives (T1), sample with addition of 20% water (T2), sample with addition of 20% water and 2% molasses (T3), samples with addition of 20% water and 4% molasses (T4), sample with addition of 20% water and 6% molasses (T5). After completion of each ensiled period, physical and nutritional properties, in-vitro digestibility and metabolizable energy were determined. The result reveals that physical properties (color, smell, softness and fungal growth) of maize stover were improved in molasses treatments. It was also improved with increasing the ensiling time from 45 to 135 days. Among the treatments T4 was found best, as there were no fungal growth. The crude protein (CP) content of maize stover was increased (P<0.01) and the dry matter (DM), organic matter (OM) and crude fibre (CF) contents were decreased (P<0.01) after ensiling and addition of molasses. The highest DM, OM and CF content was found to be 72.33, 87.70 and 37.08% in T0 and highest CP was found to be 10.67% in T4 but the lowest DM, OM, CF and CP was found to be 63.17% in T2, 82.68% in T3, 28.18% in T5 and 6.28% in T0. The DM, OM, CP and CF contents were similar (P>0.01) at different ensiling time (45 to 135 days). The OMD (organic matter digestibility) and ME (metabolizable energy) contents were increased by ensiling with molasses. The highest OMD and ME values were observed in treatment T4 which were 42.01% and 6.50 MJ/kg DM, respectively. Therefore, it can be concluded that the addition of molasses improved the physical and nutritional properties and preservation capacity of maize stover after 135 days of ensiling. DOI: http://dx.doi.org/10.3329/bjas.v37i2.9880 BJAS 2008; 37(2): 42-51